2014
DOI: 10.1186/bcr3673
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal precursor cells maintain the differentiation and proliferation potentials of breast epithelial cells

Abstract: IntroductionStromal-epithelial interactions play a fundamental role in tissue homeostasis, controlling cell proliferation and differentiation. Not surprisingly, aberrant stromal-epithelial interactions contribute to malignancies. Studies of the cellular and molecular mechanisms underlying these interactions require ex vivo experimental model systems that recapitulate the complexity of human tissue without compromising the differentiation and proliferation potentials of human primary cells.MethodsWe isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
(92 reference statements)
0
16
0
Order By: Relevance
“…Indeed, many organoid and co-culture studies have reported variable requirements for mesenchyme signaling to support epithelial progenitor cells and differentiation ex vivo (Chou et al, 2016;Hegab et al, 2015;Wells et al, 2013). Of particular note, in some studies, soluble factors can substitute for mesenchyme to promote some epithelial characteristics (Rebustini and Hoffman, 2009;Sequeira et al, 2010;Steinberg et al, 2005) and other studies demonstrate a requirement for direct contact of the mesenchyme to support epithelial differentiation (Duss et al, 2014;Lee et al, 2014;Li et al, 2004;Park et al, 2014). FGF signaling is required for development of salivary glands and other branched organs (Hoffman et al, 2002;Lombaert et al, 2013;Miralles et al, 1999;Patel et al, 2006;Steinberg et al, 2005;Zhang et al, 2014); however, the cell types that require FGF signaling are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many organoid and co-culture studies have reported variable requirements for mesenchyme signaling to support epithelial progenitor cells and differentiation ex vivo (Chou et al, 2016;Hegab et al, 2015;Wells et al, 2013). Of particular note, in some studies, soluble factors can substitute for mesenchyme to promote some epithelial characteristics (Rebustini and Hoffman, 2009;Sequeira et al, 2010;Steinberg et al, 2005) and other studies demonstrate a requirement for direct contact of the mesenchyme to support epithelial differentiation (Duss et al, 2014;Lee et al, 2014;Li et al, 2004;Park et al, 2014). FGF signaling is required for development of salivary glands and other branched organs (Hoffman et al, 2002;Lombaert et al, 2013;Miralles et al, 1999;Patel et al, 2006;Steinberg et al, 2005;Zhang et al, 2014); however, the cell types that require FGF signaling are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of INHBA in mesenchymal cells increases colony formation potential of breast epithelial cells. 24 PTN, a secretory cytokine, has been found to stimulate breast cancer progression through remodeling of the tumor microenvironment. 25 Downregulation of SIAH2 has been found to be associated with resistance to endocrine therapy in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…It is unregulated in various tumors, such as lung cancer, breast cancer, meningeal glioma and so on [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%